Gaps in provincial decision-maker's perception and knowledge of climate change adaptation in China. Issue 58 (April 2016) - Liu, Tingting; Ma, Zhongyu; Huffman, Ted; Ma, Like; Jiang, Hongqiang; Xie, Haiyan
Highlights: The understanding of climate change adaptation measures are varied among decision makers from different regions. The decision makers have the lowest understanding of measures related to human health protection. Over 90% of investigated decision makers expressed strong needs for knowledge on climate change adaptation. Lacking of training and learning materials was the main barrier to develop knowledge of climate change and adaptation. The greatest obstacle for decision makers making adaptation plans or policies was a funding shortage. Abstract: The perspectives and knowledge of decision makers, especially those at the provincial level, have great impact on the progress of climate change adaptation in China. Therefore, identifying knowledge gaps and enhancing climate adaptation awareness of decision makers at that level is very important. Based on this aim, we conducted a survey of climate change adaptation awareness among 85 administrative and management personnel from governmental departments responsible for climate change adaptation planning in five provinces. Study findings revealed that over half of respondents have knowledge of climate change adaptation measures, but the extent of understanding varied across different adaptation aspects and regions. Among the different aspects, understanding of measures related to human health protection was the lowest. A large majority of respondents indicated an eagerness to obtain knowledge and information about climate change adaptation, but the main barrier is a lack of training and learning material. When making adaptation plans or policies, the greatest obstacle expressed was a funding shortage. Information generated from this study can provide direction and guidance for training and educating provincial decision makers in order to improve the levels of adaptation planning and policy making.